2018
DOI: 10.4265/bio.23.199
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Chlorine-injured <i>Escherichia Coli</i> O157:H7 on Fresh-cut Cabbage during Cold Storage in High CO<sub>2</sub> Atmospheres

Abstract: Viability of chlorine-injured E. coli O157:H7 inoculated onto shredded cabbage was evaluated during storage in air or high CO 2 controlled atmospheres CA of 5%, 10%, and 15% at 10 and in a modified atmosphere packaging MAP at 5 and 10. When shredded cabbage was inoculated with chlorine-injured E. coli O157:H7 % injury = 65% and then stored in air or CA at 10 , counts of E. coli O157:H7 increased during storage and injured E. coli O157:H7 % injury = 34-66% were detected on samples throughout the storage regardl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…When an active MAP of 10% CO 2 in this study was compared with a passive MAP in our previous study (Izumi and Inoue, 2018b) , the trend of chlorine-injured E. coli O157:H7 that remained constant during storage at 5℃ were similar regardless of CO 2 concentration particularly in the first few days of storage. In high CO 2 atmospheres > 40%, Okon (1987) reported that inoculation of 10 8 CFU/mL of Azospirillum brasilense on tomato plants stimulated the respiration rate to a 1.7-fold increase as compared to noninoculated controls due to the increased activity of malate dehydrogenase related to TCA cycle in respiration.…”
Section: Chlorine-injured E Coli O157:h7 On Shredded Cabbage Stored I...mentioning
confidence: 47%
See 2 more Smart Citations
“…When an active MAP of 10% CO 2 in this study was compared with a passive MAP in our previous study (Izumi and Inoue, 2018b) , the trend of chlorine-injured E. coli O157:H7 that remained constant during storage at 5℃ were similar regardless of CO 2 concentration particularly in the first few days of storage. In high CO 2 atmospheres > 40%, Okon (1987) reported that inoculation of 10 8 CFU/mL of Azospirillum brasilense on tomato plants stimulated the respiration rate to a 1.7-fold increase as compared to noninoculated controls due to the increased activity of malate dehydrogenase related to TCA cycle in respiration.…”
Section: Chlorine-injured E Coli O157:h7 On Shredded Cabbage Stored I...mentioning
confidence: 47%
“…Nontoxigenic Escherichia coli O157:H7 JCM18426 obtained from the Japan Collection of Microorganisms (Riken BioResource Center, Ibaraki, Japan) were grown in tryptic soy broth (TSB; Nissui Pharmaceutical, Tokyo, Japan) and incubated at 30℃ for 24 h. Cells were washed twice in sterile saline solution (0.85% NaCl in distilled water) by centrifugation (3,000×g, 20℃ for 10 min) , and adjusted with sterile saline solution to approximately 10 8 CFU/mL. Izumi and Inoue (2018b) reported that electrolyzed water containing 0.5 to 2 ppm available chlorine caused chlorineinjury with injury level of 46 to 90% to a pure culture of E. coli O157:H7. Thus, electrolyzed strongly acidic water was diluted to the concentration of 1 ppm of available chlorine with sterile distilled water.…”
Section: Suspension Of Chlorine-injured E Coli O157:h7mentioning
confidence: 99%
See 1 more Smart Citation
“…Symbols with * indicate significant at P ≤ 0.05 between paired low and high OTR films in the same day. CA of 5%, 10%, and 15% CO 2 at 10℃ (Izumi and Inoue 2018b) . Counts of E. coli O157:H7 increased during storage of 5 days, the increase being greater in 10 and 15% CO 2 than in air and 5% CO 2 (FIG.…”
Section: Sublethally Injured Bacteria During Storage Of Fresh-cut Veg...mentioning
confidence: 92%
“…We previously reported the enumeration and identification of injured bacteria by chlorine (Izumi et al 2016b;Izumi and Inoue 2018a, 2018b, 2020 , ethanol (Inoue et al 2017) , fungicide (Izumi et al 2016b) , and cold and high CO 2 atmosphere (Izumi and Inoue 2018a, 2018b, 2020 . This review is made on our published and unpublished data on the occurrence and viability of sublethally indicator and pathogenic coliform bacteria of fresh vegetables during production and harvest and fresh-cut vegetables during processing and distribution.…”
Section: Sublethally Injured Bacteria During Production Of Vegetablesmentioning
confidence: 99%